Pengembangan Model Pembelajaran Passing Bawah Bola Voli Siswa Tunagrahita Ringan - Fadoli, Hendi Imam; Lufthansa, Luthfie (Jurnal Sporta Saintika, 2022)
Physical education learning for ABK is more in the form of movement activities in the form of games to attract more attention of ABK students in carrying out the physical education learning process. Therefore, it is necessary to make volleyball game models that can increase student enthusiasm. The method used in this research is research and development. The model used is the development of a 4-D model. The instrument used is an assessment using 2 (two) scales consisting of In accordance with the value of 1 (one) and Not in accordance with the value of 0 (zero). Where this assessment is assessed by homeroom teachers, learning experts and volleyball experts. With a small group trial subject, namely class IV students totaling 10 students. While the subject of the large group trial, namely the students of class V and class VI, totaled 23 students. The product of this development research is the Jurjit Siwali learning model for mild mentally retarded children which contains 6 learning models, namely: (1) War Ready, (2) Enemy Spying, (3) Enemy Chasing, (4) Battle, (5) Joint Formation, (6) Strategy Competition. The results of the assessment of each learning model by experts are as follows: The Ready for War Model gets a value of 100, the Enemy Scouting Model gets a score of 93, the Enemy Chasing Model gets a score of 95, the Battle Model gets a score of 93, the Joint Formation Model gets a score of 95 and the Strategy Fighting Model gets a value 90.